Trends in Austrian Resource Efficiency: An Exergy and Useful Work Analysis in Comparison to Material Use, CO2 Emissions, and Land Use. (26th September 2016) - Eisenmenger, Nina; Warr, Benjamin; Magerl, Andreas
Summary: In the past few years, resource use and resource efficiency have been implemented in the European Union (EU) environmental policy programs as well as international sustainable development programs. In their programs, the EU focuses on four resource types that should be addressed: materials, energy (or carbon dioxide [CO2 ] emissions), water, and land. In this article, we first discuss different perspectives on energy use and present the results of a long‐term exergy and useful work analysis of the Austrian economy for the period 1900–2012, using the methodology developed by Ayres and Warr. Second, we discuss Austrian resource efficiency by comparing the presented exergy and useful work data with material use, CO2 emissions, and land‐use data taken from statistical sources. This comparison provides, for the first time, a long‐term analysis of Austrian resource efficiency based on a broad understanding thereof and evaluates Austrian development in relation to EU and Austrian policy targets.